Smallholder farmers in the Great Ruaha River sub-Basin of Tanzania: coping or adapting to rainfall variability?. (16th April 2017) - Pauline, Noah M.; Vogel, Coleen; Grab, Stefan; Liwenga, Emma T.
Abstract : Climate change and variability are pervasive contemporary realities in Africa. In this paper, we investigate climate stressors (i.e. rainfall patterns and drought) that have occurred in the Great Ruaha River sub-Basin (GRRB), Tanzania. By making use of a mixed-methods approach, including both quantitative and qualitative data collection, we demonstrate that changes in rainfall pattern experienced by rural farmers in the GRRB have increased since the 1990s, as have limiting factors constraining sustainable response options. By interrogating data from focus group discussions with smallholder farmers, household questionnaire surveys, and records from government institutions, we show that sustainable livelihoods in this area are also being compromised by non-climatic stresses such as a lack of coordinated crop markets and poor access to loans, inadequate weather forecast information, and poor irrigation infrastructure and varying climate. As a consequence of climatic stresses, resources utilization, diversification of farming methods, and broader structural and development concerns, smallholder farmers have responded with corresponding changes in coping and adaptation strategies. Smallholder farmers are more frequently resorting to shorter term coping strategies rather than longer term adaptation, and are thus still heavily reliant on social, economic, and policy support to improve both their shorter term coping and longer term adaptive capacity.